Antimicrobial peptides, disease severity and exacerbations in bronchiectasis. Issue 9 (5th July 2019) - Sibila, Oriol; Perea, Lídia; Cantó, Elisabet; Shoemark, Amelia; Cassidy, Diane; Smith, Alexandria Holly; Suarez-Cuartin, Guillermo; Rodrigo-Troyano, Ana; Keir, Holly R; Oriano, Martina; Ong, Samantha; Vidal, Silvia; et al.
Abstract : Rationale: Recently a frequent exacerbator phenotype has been described in bronchiectasis, but the underlying biological mechanisms are unknown. Antimicrobial peptides (AMPs) are important in host defence against microbes but can be proinflammatory in chronic lung disease. Objectives: To determine pulmonary and systemic levels of AMP and their relationship with disease severity and future risk of exacerbations in bronchiectasis. Methods: A total of 135 adults with bronchiectasis were prospectively enrolled at three European centres. Levels of cathelicidin LL-37, lactoferrin, lysozyme and secretory leucocyte protease inhibitor (SLPI) in serum and sputum were determined at baseline by ELISA. Patients were followed up for 12 months. We examined the ability of sputum AMP to predict future exacerbation risk. Measurements and main results: AMP levels were higher in sputum than in serum, suggesting local AMP release. Patients with more severe disease at baseline had dysregulation of airway AMP. Higher LL-37 and lower SLPI levels were associated with Bronchiectasis Severity Index, lower FEV1 (forced expiratory volume in 1 s) and Pseudomonas aeruginosa infection. Low SLPI levels were also associated with the exacerbation frequency at baseline. During follow-up, higher LL-37 and lower SLPI levels were associated with a shorter time to the next exacerbation, whereas LL-37 alone predicted exacerbation frequency over the next 12 months. Conclusions: Patients with bronchiectasis showed dysregulated sputum AMP levels, characterised by elevated LL-37 and reduced SLPI levels in the frequent exacerbator phenotype. Elevated LL-37 and reduced SLPI levels are associated with Pseudomonas aeruginosa infection and can predict future risk of exacerbations in bronchiectasis.